Tiaras a history of splendour - Munn, Geoffrey C. 1953- (Antique Collectors' Club, 2018)
Tiaras have always inspired a great fascination and the most beautiful and influential women have been painted, photographed and admired whilst wearing them. Even in the twenty-first century they are still worn and continue to inspire special poise and elegance. This lavishly illustrated book includes new photographs of a variety of Royal tiaras together with those of French and Russian Imperial provenances. Geoffrey Munn has been granted special access to the photographic archives of many famous jewellers, including Cartier, Boucheron and Faberg,, for his research. Other makers include Castellani, Fouquet, Garrards, Giuliano, Lalique, and Tiffany. Among the contemporary pieces illustrated are tiaras belonging to Jamie Lee Curtis, Vivienne Westwood, Elton John and Madonna, made by Slim Barratt, Galliano and Versace
Keywords: Geschichte; Tiara; Kronjuwel; Großbritannien; USA; Russland; Frankreich; Tiaras; Tiaras / History; History; Bibliografie; Bildband